St. Joseph planning survey, 2013 - Janke, James; Trechter, David (My University, 2013)
The purpose of this study was to gather opinions from Town residents and non-resident property owners with respect to planning for the future of the Town of St. Joseph.
ii + 109 p.
Keywords: City planning--Wisconsin--St. Joseph; Land use--Wisconsin--St. Joseph; Public opinion--Wisconsin--St. Joseph; St. Joseph (Wis.)--Surveys; St. Joseph (Wis.); St. Joseph, Wisconsin; St. Croix County, Wisconsin; Town of St. Joseph comprehensive plan; Comprehensive plan; Comprehensive plan report; Community planning; Public opinion survey